Misi Yesus Melampaui Batas-Batas: Memaknai Misi Yesus dalam Konteks Lintas Budaya berdasarkan Markus 7:24-30 dan Implikasinya bagi Misi Kristen - Andri Vincent Sinaga; Roby Hendra Tumangger (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
Christian mission is often interpreted narrowly and exclusively, without considering cross-cultural contexts. Whereas Jesus Himself showed an open and inclusive attitude in His encounter with the Syro Phoenician woman in Mark 7:24-30. This study aims to explore the theological meaning of Christian mission in a cross-cultural context based on the story of Jesus and the Syrophoenician woman in Mark 7:24-30. This research uses a qualitative method with a critical discourse analysis approach to Mark 7:24-30. Data were collected through literature study. The results showed that Jesus showed an open and friendly attitude towards the Siro Phoenician women who were different in culture and religion. Jesus dared to cross the boundaries of tradition and prejudice to show God's love for all people. This study concludes that Christian mission is inclusive and transcends cultural boundaries. Christian mission is essentially a call to share the love of Christ to all people regardless of cultural or religious background.